2012
DOI: 10.4236/aim.2012.23026
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of <i>cry</i> and <i>cyt</i> Genes among Indigenous <i>Bacillus thuringiensis</i> Isolates with Mosquitocidal Activity

Abstract: Bacillus thuringiensis strains isolated from Madurai, TamilNadu, India were evaluated for their mosquitocidal activity, as well as cry and cyt genes diversity. It revealed that 99% of the parasporal crystal morphology of these isolates was spherical in nature and a variable percentage (0%-100%) of toxicity was observed against Culex quinquefasciatus and Aedes aegypti. PCR analysis revealed that 53% of the isolates were positive for the various cry and cyt genes tested, whereas 47% did not produce any PCR produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…Each of these 23 isolates and the Bti -H14 strain were tested for positive amplification of the cry and cyt and chi genes specific to Diptera using a battery of previously-described universal and specific primers [25, 3134] (Additional file 2: Table S2). All examined isolates yielded amplicons of the predicted size for cry4 , cry11 , cyt1 and cyt2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these 23 isolates and the Bti -H14 strain were tested for positive amplification of the cry and cyt and chi genes specific to Diptera using a battery of previously-described universal and specific primers [25, 3134] (Additional file 2: Table S2). All examined isolates yielded amplicons of the predicted size for cry4 , cry11 , cyt1 and cyt2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotide primers were synthesized in a DNA synthesizer (Applied Biosystems, Foster City, CA, USA) using the manufacturer’s instructions. PCR amplifications were performed as previously described [25] and the resulting amplicons were visualized by running the PCR products (15μl) on 2% agarose electrophoretic gels as described in Mahalakshmi et al [34]. …”
Section: Methodsmentioning
confidence: 99%
“…For example, the expression of cry4 , cry10 , or cry11 genes give rise to spherical shape crystals, and their respective proteins are known to be active against Diptera [73,74,75,76]. Crystals with a bipyramidal shape result from the accumulation of Cry1 or Cry9 proteins, which are active mainly against Lepidoptera [24,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to smooth colonies with irregular shape, Lima et al (2002) also characterized a B. thuringiensis isolate that produced dark yellowish colonies. Apart from the characteristics stated, many also reported that B. thuringiensis strains formed "fried-egg" appearance on agar plate (Travers et al, 1987;El-kersh et al, 2012;Mahalakshmi et al, 2012). The descriptions for colony morphology are very subjective.…”
Section: Discussionmentioning
confidence: 99%